GAS6 receptor status is associated with dormancy and bone metastatic tumor formation. - Russell S Taichman (PLoS ONE, 2013)
Disseminated tumor cells (DTCs) are believed to lie dormant in the marrow before they can be activated to form metastases. How DTCs become dormant in the marrow and how dormant DTCs escape dormancy remains unclear. Recent work has shown that prostate cancer (PCa) cell lines express the growth-arrest specific 6 (GAS6) receptors Axl, Tyro3, and Mer, and become growth arrested in response to GAS6. We therefore hypothesized that GAS6 signaling regulates the proliferative activity of DTCs in the marrow. To explore this possibility, in vivo studies were performed where it was observed that when Tyro3 expression levels exceed Axl expression, the PCa cells exhibit rapid growth. When when Axl levels predominate, PCa cells remain largely quiescent. These findings suggest that a balance between the expression of Axl and Tyro3 is associated with a molecular switch between a dormant and a proliferative phenotype in PCa metastases.